The causes of temporary sport dysmnesia in trampoline athletes - Ren, Z.; Lin, C.; Ren, J. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The trampoline requires athletes to be adept physically, technically and psychologically. Athletes bear physical and psychological burdens throughout years of training, and it can contribute to a psychological problem known as Temporary Sport Dysmnesia (TSD). TSD can affect the technical mastery of athletes and therefore it is necessary to thoroughly research this problem.